2012
DOI: 10.1016/j.forsciint.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The PMMA epidemic in Norway: Comparison of fatal and non-fatal intoxications

Abstract: During a 6 month period (July 2010-January 2011) we observed 12 fatal intoxications and 22 non-fatal cases related to the drug paramethoxymethamphetamine (PMMA) in Norway (4.8 mill inhabitants). This toxic designer drug, also known as "Death", is occasionally found in street drugs offered as "ecstasy" or "amphetamine". The present study aimed to evaluate the cause of death, and to compare the PMMA blood concentrations in fatal and non-fatal cases. Methods for identification and quantification of PMMA are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 27 publications
2
38
0
1
Order By: Relevance
“…These pills mainly contain the empathogenic substance MDMA (3,4-methylenedioxy-N-methylamphetamine; 'Ecstasy') or PMA (para-methoxy-amphetamine); PMA is a serotonergic substance of the amphetamine class, with psychedelic and antidepressant properties; it first came into circulation in the early 1970s, when it was used as an alternative to LSD for its hallucinogenic effects. Since the 70s it caused more than 90 deaths in Canada, USA, Australia and Europe (Vevelstad et al 2012), mostly related to the consequences of acute temperature elevation (hypertemia) leading to multi-organ failure occurring at dosages only slightly above the usual recreational range.…”
Section: Appearance Of Nps and Packagingmentioning
confidence: 99%
“…These pills mainly contain the empathogenic substance MDMA (3,4-methylenedioxy-N-methylamphetamine; 'Ecstasy') or PMA (para-methoxy-amphetamine); PMA is a serotonergic substance of the amphetamine class, with psychedelic and antidepressant properties; it first came into circulation in the early 1970s, when it was used as an alternative to LSD for its hallucinogenic effects. Since the 70s it caused more than 90 deaths in Canada, USA, Australia and Europe (Vevelstad et al 2012), mostly related to the consequences of acute temperature elevation (hypertemia) leading to multi-organ failure occurring at dosages only slightly above the usual recreational range.…”
Section: Appearance Of Nps and Packagingmentioning
confidence: 99%
“…The main families monitored by EU Early Warning System (EWS) since 2005 include synthetic cannabinoids, phenethylamines, other substances (derivatives, medicinal products, intermediates and precursors), arylalkylamines, cathinones, opioids, benzodiazepines, tryptamines, aminoindanes, arylcyclohexylamines, piperazines, piperidines, pyrrolidines, and plants and extracts . Often, NPS are easily acquired legally through the Internet and smart shops where they are sold under various product labels with misleading information about their effects and safety . They are considered a growing problem in many communities and are responsible for numerous fatal intoxications …”
Section: Introductionmentioning
confidence: 99%
“…Vevelstad et al [30] reported 12 fatal intoxications related to PMMA in Norway during a 6-month period (July 2010-January 2011). PMMA is the 4-methoxy analogue of methamphetamine, and PMA (paramethoxyamphetamine), its toxic metabolite, is the 4-methoxy analogue of amphetamine.…”
Section: Pmma (Paramethoxymethamphetamine)mentioning
confidence: 99%